Evaluation of 18F-EF5 for detection of hypoxia in localized adenocarcinoma of the prostate. (2nd November 2021) - Wadsworth, Brennan J.; Decotret, Lisa R.; Villamil, Carlos; Yapp, Donald; Wilson, Don; Benard, Francois; McKenzie, Michael; Bennewith, Kevin L.
Abstract: Background: A common feature of solid tumours that are resistant to therapy is the presence of regions with low oxygen content (i.e., hypoxia). Oxygen electrode studies suggest that localized prostate adenocarcinoma is commonly hypoxic, although conflicting data have been reported between immunohistochemical detection of hypoxia-induced proteins in biopsy specimens and positron emission tomography (PET) imaging of 18 F-labeled hypoxia reporters. Although the 2-nitroimidazole 18 F-EF5 is well-established to label hypoxic tumour cells in pre-clinical tumour models and clinical trials of multiple primary tumour sites, it has yet to be tested in prostate cancer. The purpose of this study was to evaluate the feasibility of using 18 F-EF5 to detect hypoxia in clinical prostate tumours. Material and methods: Patients with localized adenocarcinoma of the prostate were recruited for pre-treatment 18 F-EF5 PET scans. Immunohistochemistry was conducted on diagnostic biopsies to assess the expression of glucose transporter 1 (GLUT1), osteopontin (OPN), and carbonic anhydrase IX (CAIX). Immunoreactivity scores of staining intensity and frequency were used to indicate the presence of tumour hypoxia. Results: We found low tumour-to-muscle ratios of 18 F-EF5 uptake that were not consistent with tumour hypoxia, causing early termination of the study. However, we observed GLUT1 and OPN expression in all prostate tumour biopsies, indicating the presence of hypoxia in all tumours. Conclusion: Our data do not support the use of 18 F-EF5 PET to detect hypoxia in prostate adenocarcinoma, and suggest the use of immunohistochemistry to quantify expression of the hypoxia-inducible proteins GLUT1 and OPN as indications of prostate tumour hypoxia.